Sedimentary architecture and evolution of a Quaternary sand-rich submarine fan in the South China Sea - Liu, Entao; Yan, Detian; Pei, Jianxiang; Lin, Xudong; Zhang, Junfeng (Frontiers in Marine Science, 2023)
Investigating the sedimentary architecture and evolution of sand-rich submarine fans is vital for comprehending deep-water sedimentary processes and enhancing the success rate of hydrocarbon resource exploration. Recent drilling activities in the Qiongdongnan Basin, northern South China Sea, have unveiled significant gas hydrate and shallow gas potential. However, exploration in this area faces substantial challenges due to the limited understanding of sandy reservoirs. Leveraging extensive newly acquired extensive 3D seismic data ( 9000 km2) and well data, our study reveals five distinct deep-water depositional systems in the Quaternary Ledong Formation, including a submarine fan system, mass transport deposits, deepwater channel-levee systems, slope fans, and hemipelagic sediments. Notably, the targeted sand-rich submarine fan lies within the abyssal plain, situated at a water depth of 1300-1700 m. This fan exhibits a unique tongue-shape configuration and a SW-NE flow direction within the plane and spans an expansive area of 2800 km2 with maximum length and width reaching 140 km and 35 km, respectively. Vertically, the fan comprises five stages of distributary channel-lobe complexes, progressing from Unit 1 to Unit 5. Their distribution ranges steadily increase from Unit 1 to Unit 3, followed by a rapid decrease from Unit 4 to Unit 5. Our results suggest that the occurrence and evolution of the submarine fan are primarily controlled by sea level fluctuation, confined geomorphology, and sediment supply. Specifically, sea level fluctuation and sediment supply influenced the occurrence of the submarine fan. Concurrently, the confined geomorphology in the abyssal plain provided accumulation space for sediments and shaped the fan into its distinct tongue-like form. In contrast to the deepwater channels within the deepwater channel-levee systems, the distributary turbidite channels within the submarine fan are marked by lower erosion depth with “U” shapes, greater channel width, and higher ratios of width to depth. The comparative analysis identifies turbidite channels as the focal points for offshore gas hydrate and shallow gas exploration in the Qiongdongnan Basin. Furthermore, the temporal evolution of submarine fan offers valuable insights into Quaternary deep-water sedimentary processes and hydrocarbon exploration within shallow strata of marginal ocean basins.